Dinamika Kelas Sosial Masyarakat Di Kesultanan Palembang Darussalam Pada Masa Transisi - Lian Fitriana Sari; Mohammad Syawaludin; Sholeh Khudin (Tanjak: Sejarah dan Peradaban Islam, 2021)
Stratification and social class are two different things but are very often used interchangeably. Class has a narrower meaning than social stratification. if class is more specific then stratification has a broader meaning because it refers more to the division of a group of people or society at their respective levels. And this belongs to the layers that exist in society. Something similar like this of course also happened to the people of the Sultanate of Palembang Darusslam. Moreover, Palembang has a strategic location which makes its port so that it can be said to be in the international arena which makes traders from outside also come. So it does not rule out if the European nation is interested in both agricultural products and areas from Palembang. This research tries to be able to better explain the social conditions that existed in society during the Palembang Darussalam sultanate during the transition period to be precise. So the researchers hope that this can be a way of knowing more about the history of the Palembang Darussalam sultanate in transition and also being one of the categories of preservation of Palembang history